Sistem inventory pengendalian persediaan fast moving spare part dump truck barbasis metode min-max stock - Nurul Hidayati; Braam Delfian Prihadianto (Jurnal Teknik Mesin Indonesia, 2023)
Maintenance management encompasses a series of activities that include planning, directing, implementation, control, and evaluation aimed at improving the condition of specific facilities to achieve predefined targets. This research aims to analyze the demand levels for fast-moving spare parts in dump truck units, determine the minimum and maximum spare parts inventory levels required in the warehouse, and provide recommendations to PT AHG regarding spare parts inventory management based on the min-max method with the development of a safety inventory information system. In the company's previous management, no systematic approach was applied to address these fluctuations, and it needs to be developed through a more adaptive method. The research methodology employed is quantitative, integrating inventory management with other policies, including observation, interviews, and data collection and processing. The data used includes spare parts usage data from January to December 2022, focusing on oil filters, fuel filters, and brake pads in dump truck units. The analysis results indicate significant fluctuations in the demand levels of fast-moving spare parts in dump trucks throughout the period from January to December 2022, especially at the beginning and end of the year. These fluctuations are likely influenced by seasonal factors, holiday periods, and the requirements of new projects affecting the demand for spare parts in maintenance and repair activities.